2013
DOI: 10.1080/14942119.2013.844884
|View full text |Cite
|
Sign up to set email alerts
|

Mechanized tree planting with an excavator-mounted M-Planter planting device

Abstract: The efficiency of modern tree planting machines is strongly affected by operational conditions, technical machine performance, and operator. In this study, the aim was to determine the time consumption of mechanical planting work using the M-Planter planting machine in Finnish regeneration areas where stumps were harvested and slash collected. The work of six operators, working with four M-Planter planting machines, was quantified with a stopwatch-study method. A linear mixed-effects model was used to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 8 publications
(27 reference statements)
1
15
0
Order By: Relevance
“…Nevertheless, simply understanding that efficient seedling logistics is also a responsibility of the forest company might lead to greater efforts by the forest company [18]. Similar to all mechanized forestry work [37,38], the operator's skill level has a profound effect on planting machine productivity [12,14]. Thus, profitable mechanized tree planting requires access to skilled operators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, simply understanding that efficient seedling logistics is also a responsibility of the forest company might lead to greater efforts by the forest company [18]. Similar to all mechanized forestry work [37,38], the operator's skill level has a profound effect on planting machine productivity [12,14]. Thus, profitable mechanized tree planting requires access to skilled operators.…”
Section: Discussionmentioning
confidence: 99%
“…Cost-efficiency is hampered by low productivity, which originates from operator inexperience, among other reasons [12]. The choice of worksites also strongly influences productivity, and it has been reported that the presence of stones, slash, and stumps decreases the planting machines' productivity [13][14][15][16][17]. The size and spatial distribution of worksites also affects cost-competitiveness [18].…”
Section: Introductionmentioning
confidence: 99%
“…A second recommendation would be that a careful appraisal of worksite suitability for mechanized planting is important because stoniness, stumps and slash debris significantly diminish productivity (Saarinen 2006;Rantala et al 2009;Rantala and Laine 2010;Laine and Rantala 2013;Ersson 2014). Also, by avoiding small worksites and optimizing the number of and distance between machine relocations, mechanized planting can become more efficient (Rantala et al 2009;Hallongren et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanized tree planting is growing in Finland as well; there mainly because of dwindling supplies of manual tree planters and ambitions to decrease silvicultural costs (Rantala and Laine 2010;Laine and Rantala 2013). However, in both countries, mechanized planting tends to be more expensive than mechanized soil preparation and manual planting, and much of this added expense can be attributable to the planting machines' low productivities (Ersson 2010;Strandström et al 2011).…”
Section: Introductionmentioning
confidence: 99%